PENGARUH KOMUNIKASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN RS SURYA MELATI NGLETIH - Nurlelasari, Fitri Endah; Astuti, Indah Yuni; Widuri, Trisna; Yuliyanti, Rahma (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to determine : (1) the influence of communication (X1) on employee performance (Y), (2) the effect of work stress (X2) on employee performance (Y). This type of research is a quantitative approach. The population in this study were all employees of Surya Melati Ngletih Hospital, namely 116 people. The sample in this study was the total number of employees in the nurse section consisting of 34 nurses at Surya Melati Ngletih Hospital. The sampling technique uses purposive sampling. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of the study at the level of 5% indicate that (1) There is a positive and significant partial effect between communication (X1) on employee performance at Surya Melati Ngletih Hospital. The value of t arithmetic 2.916 and a significant value of 0.007 <0.05. (2) There is a positive and not significant partial effect between work stress (X2) on employee church at Surya Melati Ngletih Hospital. The value of t count is 1.831 and the significant value is 0.077> 0.005. (3) There is a positive and significant influence between communication (X1) and work stress (X2) simultaneously on employee performance at Surya Melati Ngletih Hospital. This is proven by the calculated F value of 24,650 and the significant value of F is 0,000. The calculation of multiple linear regression analysis using the regression equation is obtained by the value Y = 3.127 + 0.653X1 + 0.159x2.